2016
DOI: 10.1080/2162402x.2016.1219825
|View full text |Cite
|
Sign up to set email alerts
|

HLA class I-restricted MYD88 L265P-derived peptides as specific targets for lymphoma immunotherapy

Abstract: Genome sequencing has uncovered an array of recurring somatic mutations in different non-Hodgkin lymphoma (NHL) subtypes. If affecting protein-coding regions, such mutations may yield mutation-derived peptides that may be presented by HLA class I proteins and recognized by cytotoxic T cells. A recurring somatic and oncogenic driver mutation of the Toll-like receptor adaptor protein MYD88, Leu265Pro (L265P) was identified in up to 90% of different NHL subtype patients. We therefore screened the potential of MYD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…Rosenberg's team identified time in which the T cells were stimulated by antigens in vitro are a key factor affecting the immune responses. For instance, T cell responses observed after several approximately 3-week rounds of stimulations based on artificial APCs or irradiated APCs were confirmed to be mediated by de novo-primed naive T cells rather than by preexisting memory T cells, as short-time stimulation of the same PBMCs did not result in the detection of specific T cell clones (28)(29)(30). In this study, the neoantigen identification was based on the detection of spontaneous memory T cell responses, which may be more suitable for refractory advanced solid tumors with very short survival time: (a) A therapeutic vaccine for preexisting antigen-specific T cells, which were produced as a secondary immune response after vaccination, was more rapid and more intense.…”
Section: Discussionmentioning
confidence: 97%
“…Rosenberg's team identified time in which the T cells were stimulated by antigens in vitro are a key factor affecting the immune responses. For instance, T cell responses observed after several approximately 3-week rounds of stimulations based on artificial APCs or irradiated APCs were confirmed to be mediated by de novo-primed naive T cells rather than by preexisting memory T cells, as short-time stimulation of the same PBMCs did not result in the detection of specific T cell clones (28)(29)(30). In this study, the neoantigen identification was based on the detection of spontaneous memory T cell responses, which may be more suitable for refractory advanced solid tumors with very short survival time: (a) A therapeutic vaccine for preexisting antigen-specific T cells, which were produced as a secondary immune response after vaccination, was more rapid and more intense.…”
Section: Discussionmentioning
confidence: 97%
“…Tumor-specific neoepitopes can derive from protein-alteration mutational events. Nelde et al have identified a set of HLA class 1 MyD88 L265P-derived ligands that elicit specific T cell responses [28]. These data highlight the potential of MyD88 L265P-mutation-specific peptides-based immunotherapy as a novel personalized treatment approach.…”
Section: Tlr Inhibitorsmentioning
confidence: 98%
“…However, it is difficult to detect neoantigens in cancer cells with a low mutation load, although neoantigens also occur (38,39), but in this condition, this method cannot distinguish them from normal peptides. In addition, most neoantigens are unique to one special patient, although there are some neoantigens, such as the MYD88 L265P mutation, the histone 3 variant H3.3 K27M mutation, and the KRAS G12D hotspot-driver mutation, that are present in several patients (40)(41)(42). Even in the same cancer entity, the distribution of neoantigens is heterogeneous, which hinders the application of single anti-cancer drugs and creates an intractable problem in cancer treatment.…”
Section: Obstacles To This Strategymentioning
confidence: 99%
“…As MYD88 L265P is a widely occurring and tumor-specific mutation in NHL, Nelde et al predicted potential MYD88 L265P -containing HLA ligands for several HLA class I restrictions in silico. Three HLA-B * 07restricted peptides and one HLA-B * 15-restricted peptide were identified, and they found that MYD88 L265P -derived peptides can induce mutation-specific and functional immune responses in vitro (41).…”
Section: Myd88 Mutantmentioning
confidence: 99%